Improving the Development of Listening to 3-4 Years Old Children through Storytelling Methods - Annisa Herlida Sari (Universitas Muhammadiyah Ponorogo, 2020)
The purpose of this study is to describe the process and learning outcomes using storytelling methods that can improve the development of listening to children aged 3-4 years in PAUD Ceria Banjarrejo Lampung Timur. The data analysis techniques used in this study are qualitative and quantitative data analysis. Qualitative data analysis is used to collect data through field notes, observation sheets, interview notes, and documentation record. Quantitative data analysis is used to find out the percentage improvement in listening development of children after the action using the storytelling method. The results of this study indicate that there is an increase in the development of listening to children using the storytelling method. In the first cycle, an increase of 63% was obtained and increased to 83% in the second cycle. Based on these quantitative data, it is strengthened by qualitative data findings that the method of storytelling can improve the development of listening to children aged 3-4 years in PAUD Ceria Banjarrejo, East Lampung. The implication of the results of this study is that in the process of early childhood learning, it must apply methods and media that are appropriate to the stage of the child's age and be done in a fun way so that early childhood is able to absorb and optimize all aspects of development.